Atividades para idosos: um estudo de representações sociais - Costa, Sônia Mara Gusmão (2013)
Introduction: the concept of activity encompasses the sense of occupation of a person, engage in diversified activities, as well as the ability to act. The combination of increased life expectancy, declining birth rates and technological advances in the area of health sciences has led to an ever changing demographic, this dynamic translates into greater demand for health services by the elderly, bringing challenges to social and economic demands as well as a series of questions for managers and researchers in the health field. Thus, the social representations of the activities offered to seniors as forms of knowledge / information built and / or updated in the social life of the people, enables such phenomena evidencing subjective aspects involved in the daily organization of their own knowledge of a social reality. Study Objective: To identify the social representations of activities built by seniors. Methodology: this is an exploratory study of quantitative and qualitative approach, developed with older people (N = 240). For data collection we used a semistructured interview and test the Free Word Association with the term inductor activities offered to seniors. The data obtained from the interviews and said test were organized in databases and processed by software Alceste 4.8 and SPSS 20. Results: There was a predominance of elderly females, 70-74 years old, widowed and married elderly, women with average education and men with low education and income equivalent to the minimum wage, with respect to activities 17.9% did not hold no activity. The data obtained from the analysis of the Alceste, with a rate of 91.25% of the analyzed material included seven classes: social dimensions, physical, psychological, psychosocial, types of activities; opinions on activities and benefits of the activity. Final considerations: to identify the social representations of activities offered to the elderly, it is believed that this study will add value to the production of knowledge in nursing and health by knowing what the elderly think about the activities and the possibility of introducing approaches in service point of view unique and integral to the elderly.